Immunity Clause in The 1945 Constitution of The Republic of Indonesia - Baharuddin Riqiey; Vieta Imelda Cornelis; Duke Arie Widagdo; Rizky Bangun Wibisono (APHTN-HAN, 2026)
Indonesia is a country with a written constitution that contains various substantive provisions governing state structure, the distribution of power, human rights, and limitations on authority. Among these provisions are norms that grant immunity to certain state institutions, commonly referred to as immunity clauses. In the Indonesian constitutional context, immunity clauses are reflected in Article 7C and Article 20A paragraph (3) of the 1945 Constitution of the Republic of Indonesia. These provisions grant immunity to the House of Representatives (DPR), both institutionally and individually to its members. This raises an important constitutional question as to whether the existence of such immunity clauses is compatible with the principle of equality before the law. This study employs doctrinal legal research using statutory, conceptual, and historical approaches. The findings demonstrate that Article 7C constitutes a logical consequence of Indonesia’s presidential system, under which the President is constitutionally prohibited from dissolving the DPR. Furthermore, the immunity granted under Article 7C and Article 20A paragraph (3) does not contradict the principle of equality before the law, as such immunity is not absolute, remains subject to good faith, and does not preclude legal or ethical accountability for actions taken outside constitutional authority.